Effects of exogenous oxytocin and atosiban antagonist on GABA in different region of brain - Thakur, Pratibha (IBRO Rep, 2019)
Gamma amino butyric acid (GABA) is the primary inhibitory neurotransmitter in the vertebral central nervous system. It functions by altering the membrane conductance of Cl(−) ions, maintaining the membrane potential close to the resting potential. The hormone oxytocin (OT) has a central action where it acts as a neuromodulatory peptide and exerts its action depending upon the distribution of OT receptors (OTR) in the target site. OTRs are G-protein-coupled receptors (GPCRs) comprising different subunits (Gq, Gi, and Gs). The G- protein isoforms have the ability to activate different pathways, but specific agonists and antagonists may show different affinities to OTRs, depending on the specific G-protein isoform to which they are coupled. It is well documented that OTR distribution varies with age and species and in regions of the brain. In this study, we attempted to observe the impact of OT and atosiban (OTA), an OT antagonist, on GABA levels in different regions of the brain. Study animals were exposed intraperitoneally (i.p.) to normal saline (0.89%), OT 0.0116 mg/kg, and OTA 1 mg/kg in different combinations, for 30days. It was observed that OT and OTA administration modulated GABA levels in different regions of brain, while normal saline had no effect. It may be due to OTR receptor expression in different regions of the brain. This is significant because region-specific expression of different receptors could be important in the development of new drugs targeting specific neuropsychiatric disorders.